2021
DOI: 10.3390/ijms222011163
|View full text |Cite
|
Sign up to set email alerts
|

Phytoconstituents and Bioactivity of Plants of the Genus Spiraea L. (Rosaceae): A Review

Abstract: The genus Spiraea L. belongs to the Rosaceae Juss. family and includes more than 100 species distributed in the temperate zone and subtropical zone of the Northern Hemisphere at the center of species diversity in East Asia. Representatives of the genus are known as ornamental plants with many forms and varieties, are widely used in conventional medicine, and have a high resource potential. This review provides information on the diversity of phenolic compounds (flavonoids, phenolcarboxylic acids, and lignans),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 111 publications
(166 reference statements)
0
11
0
Order By: Relevance
“…Regarding the set of flavonoid compounds in Spiraea species, quercetin has proved to be the most common substance (in 21 species) in various studies; hyperoside has been detected in 14 species; isoquercitrin has been identified in 10 Spiraea species; and avicularin, rutin, and isorhamnetin have been found in 10 species by various authors [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the set of flavonoid compounds in Spiraea species, quercetin has proved to be the most common substance (in 21 species) in various studies; hyperoside has been detected in 14 species; isoquercitrin has been identified in 10 Spiraea species; and avicularin, rutin, and isorhamnetin have been found in 10 species by various authors [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lapteva concluded that this genus’s flavonoid compounds are mainly represented by flavonols, with quercetin accounting for 50% to 90% of aglycons, and the remaining flavonoid compounds are represented by kaempferol and isorhamnetin and their derivatives [ 24 ]. A literature review of the chemical composition of Spiraea species also showed that the majority (over 25) of flavonoid compounds are quercetin and its derivatives [ 25 ]. During an investigation of the chemical composition of some Spiraea species, we attempted to study phenolic components of Spiraea representatives from Asian Russia, including Spiraea hypericifolia L. [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spiraea L. is a genus of deciduous shrubs of Rosaceae tribe Spiraeeae (subfamily Amygdaloideae), which is widespread in the Northern Hemisphere [ 1 , 2 ]. East Asia has become the center of the diversity of this genus.…”
Section: Introductionmentioning
confidence: 99%
“…Many Spiraea species are applied in landscaping owing to the variations in morphological characteristics. For example, they have a high accumulated flower abundance and different flower colours in simple and compound inflorescences [ 2 ]. Moreover, representatives of the genus are widely used in conventional medicine, with several effective therapeutics for inflammation and malaria [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The extensive resource base and diverse pharmacological activities of representatives of the genus Spiraea suggest that S. hypericifolia and S. crenata are potential sources of biologically active substances with varying activities. Because the main active ingredients in Spiraea members are flavonoids and phenolcarboxylic acids, [ 16 , 17 , 26 ], our work aimed to determine the levels of phenolic compounds in water–ethanol extracts of S. hypericifolia and S. crenata and assess the antioxidant and cytotoxic properties of these extracts.…”
Section: Introductionmentioning
confidence: 99%